Perancangan Website Streaming Anime dan Manga Reader “Yonnime” Menggunakan Metode Requirement Prototyping - Alexander Wirapraja; Rizky Basatha; Daniel Fabio Santoso (G-Tech: Jurnal Teknologi Terapan, 2024)
Anime is a moving image created from various photographed or computer-generated images, using an animation style adopted from Japan and characterized by colorful graphics depicting lively characters in an action-packed plot that often uses fantastical or futuristic themes. In 2020, the number of anime and manga fans doubled from 63% to 67%. This research is the design of a streaming anime and manga reader website with the aim of increasing convenience for anime and manga fans in getting the entertainment content they are looking for. In creating the system, the requirements prototyping software development method was used. The result of this design is that the website can be used to access manga reader and anime streaming content which can be filtered using age restriction mode.